Sifat Fisik Wafer Berbahan Silase Limbah Sayur Kol dengan Jenis Kemasan dan Komposisi Konsentrat yang Berbeda - Harahap, Anwar Efendi; Adelina, Triani; Ali, Arsyadi; Mucra, Dewi Ananda; Ramadani, Dini (Buletin Peternakan Tropis, 2021)
This research aims to know the physical quality of color, aroma, texture, density, and absorption of water and know the best type of packaging in wafers resulting from vegetable waste silage cabbage. This study used a Complete Randomized Design (RAL) factorial pattern (4×2) with 2 replication. Factor A consists of concentrate composition, A0=silage of cabbage waste 100% : A1= silage of cabbage waste 75% + 25% rice bran: A2 = silage of cabbage waste 50% + 50% rice bran : A3 = silage of cabbage waste 25% + 75% rice bran and factor B consists of B0 = Bag packaging type and B1=Plastic sack packaging type. Observed parameters include color, aroma, texture, density and water absorption. The results showed that there was interaction (P>0.01) between different types of packaging and substrate composition. No interaction (P>0.05) color, density, water absorption and texture. The composition factor of the substrate has a effect (P<0.01) on color, aroma and texture, but has no effect (P>0.05) on water density and absorption. Packaging type factors have a noticeable effect (P<0.01) on color and aroma, but have no  effect (P>0.05) on density, water absorption and texture. It can be concluded that the treatment that gives the best results is the substrate composition of 25% cabbage vegetable waste + 75% rice bran and the type of jute bag packaging for 14 days of storage can maintain the physical quality of the wafer resulting from the silage of cabbage vegetable waste